2013
DOI: 10.1186/1471-2164-14-530
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive metatranscriptome analysis pipeline and its validation using human small intestine microbiota datasets

Abstract: Background: Next generation sequencing (NGS) technologies can be applied in complex microbial ecosystems for metatranscriptome analysis by employing direct cDNA sequencing, which is known as RNA sequencing (RNA-seq). RNA-seq generates large datasets of great complexity, the comprehensive interpretation of which requires a reliable bioinformatic pipeline. In this study, we focus on the development of such a metatranscriptome pipeline, which we validate using Illumina RNA-seq datasets derived from the small inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 56 publications
(75 reference statements)
2
107
0
Order By: Relevance
“…Another recent study correlated the prevalence of hepatic cancer in mice to deoxycholic acid, a secondary bile acid produced by certain members of the gut microbiota (Yoshimoto et al, 2013). A recent metatranscriptomic study showed the expression of genes matching the COG category “secondary metabolites biosynthesis, transport, and catabolism”, which is consistent with the possibility of small molecule production but could also indicate the expression of catabolic and/or transport genes unrelated to biosynthesis (Leimena et al, 2013). These examples raise the question of whether there exists a much larger set of bacterially produced molecules that mediate microbiota-host interactions.…”
Section: Introductionmentioning
confidence: 84%
“…Another recent study correlated the prevalence of hepatic cancer in mice to deoxycholic acid, a secondary bile acid produced by certain members of the gut microbiota (Yoshimoto et al, 2013). A recent metatranscriptomic study showed the expression of genes matching the COG category “secondary metabolites biosynthesis, transport, and catabolism”, which is consistent with the possibility of small molecule production but could also indicate the expression of catabolic and/or transport genes unrelated to biosynthesis (Leimena et al, 2013). These examples raise the question of whether there exists a much larger set of bacterially produced molecules that mediate microbiota-host interactions.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies in relevant scientific fields reported contradictory findings; Leimena et al, 38 found a substantial similarity between results obtained from the metatranscriptome and the metagenome of gut microbiome, while other investigations on the same topic showed the presence of a specific fraction of species that are inactive. 8,39 Our analysis showed that the entire microbial community is active and thus the presence of GBs with an extremely low transcriptional activity was not evidenced (Figures 3 and 4).…”
Section: Environmental Science and Technologymentioning
confidence: 90%
“…The functional aspect of the microbial communities in the natural environment is better elucidated by analyzing the mRNA profiles; hence, here, we applied the metatranscriptomic approach to investigate the functional gene encoding enzymes associated with the anaerobic metabolic processes of the hot spring microbiomes. Phylogenetic and functional assignments were obtained by directly aligning the mRNA reads to the complete NCBI prokaryote genome database that includes draft genomes (Leimena et al 2013).…”
Section: Discussionmentioning
confidence: 99%